ANALISIS NILAI-NILAI KARAKTER ANAK DALAM NOVEL DUNIA KECIL KARYA YOYON INDRA JONI DAN IMPLIKASINYA TERHADAP PENGEMBANGAN LITERASI BACA TULIS - Darmanto Darmanto; Fauzi Muharom (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2021)
This study aims to find out 1) the values of children's characters contained in the Dunia Kecil novel, 2) the implications of children's character values in Dunia Kecil novel on the development of literacy.This research uses library research, a research that makes library materials as a source of reference. The primary source of this research is Dunia Kecil novel by Yoyon Indra Joni while the secondary sources of this research include books, journals or other library materials that support the research and strengthen the theory. Documentations are used as a data collection method. Triangulation techniques are used to test the validity of the data. And content analytics to analyze the data.The results of the study obtained that the values of children's characters in Dunia Kecil novel are: 1) perseverance, 2) initiative, 3) researching (curiosity), 4) leadership, and the implications of the values of children's characters in Dunia Kecil novel have enormous implications on the development of literacy Because through the implantation of characters in the novel, it is able to grow children's motivation in developing reading skills and understanding the readings being studied, then it can be said that character values ​​and literacy are likened to an interconnected circle. Keywords: Character value, Development of Literacy